The Varignano section (Trento Province, northern Italy): a chance to correlate shallow benthic zones and calcareous plankton zones near the Bartonian–Priabonian boundary - PAPAZZONI, Cesare Andrea; Moretti A.; Luciani V.; Fornaciari E.; Giusberti L. (Rendiconti online della Società Geologica Italiana, 2014)
The GSSP for the base of the Priabonian stage has not yet been defined, but a candidate section has been recently proposed by Agnini et al. (2011) near Alano di Piave (Veneto region, northern Italy), some 50 km far from the historical stage stratotype of Priabona. The Alano section, deposited in a bathyal setting, has been investigated for the calcareous nannoplankton, planktonic foraminifera, as well as magnetostratigraphy. The ‘Tiziano bed’, a prominent lithological tuff layer whose base has been proposed for the base of the Priabonian (Agnini et al., 2011) is very close to different events, namely the Cribrocentrum erbae acme (Fornaciari et al., 2010; Agnini et al., 2011), the extinction of morozovellids and large acarininids (Agnini et al., 2011; Wade et al., 2012), and the base of magnetochron C17n.1n (Vandenberghe et al., 2012). Unfortunately, at Alano di Piave there is no way to directly correlate any of these events with the larger foraminifera shallow-water biozones, namely the Shallow Benthic Zones (SBZ) of Serra-Kiel et al. (1998). In the lower part of the Alano section, two coarse-grained bioclastic levels indeed contain larger foraminifera, but they both belong to the SBZ 17 (lower Bartonian). Moreover, these beds are at least 25 m below the extinction of muricate planktonic foraminifera, the lowest event that could approximate the base of the Priabonian. However, a unique chance for a direct correlation between the SBZ and the calcareous plankton zones is provided by the Varignano section (Trento Province, northern Italy), which is 80 km west of Alano di Piave, deposited in a similar bathyal setting but with much more larger-foraminiferal bearing bioclastic levels (eleven sampled). The Varignano section was first studied by Luciani & Lucchi Garavello (1986) and recently re-sampled in its Middle-Upper Eocene part on a thickness of more than 25 m. The coarse-grained levels are quite evenly distributed from base to top of this interval, intercalated with the hemipelagic sediments. In the lowermost ...